Karakteristik Morfometri dan Hubungannya dengan Kejadian Banjir di DAS Paguyaman, Gorontalo - Karina Meiyanti Maulana; Ahmad Syamsu Rijal S; Talha Dangkua; Risman Jaya; Andrew Mulabbi (Postgraduate, University of Mataram, 2025)
The Paguyaman Watershed represents a strategically significant and essential water resource for the surrounding region. In recent years, this area has become increasingly vulnerable to environmental pressures, including heightened sedimentation, changes in land use, declining water quality, and more frequent flooding events. This study aims to evaluate the morphometric characteristics of the Paguyaman Watershed and their relationship to flood vulnerability observed over the past five years. Morphometric analysis was conducted using quantitative methods within GIS and remote sensing approach. The primary dataset utilized was DEMNAS. The analyzed morphometric parameters include drainage density (3.95), stream frequency (8.61), bifurcation ratio (8.41), form factor (0.13), elongation ratio (0.40), and ruggedness number (8.20). These parameter values indicate that the Paguyaman Watershed possesses an elongated concave shape, steep topography, high surface runoff intensity, and low infiltration capacity. The findings reveal that the watershed exhibits characteristics of high flood susceptibility, as evidenced by recurrent flood events in the villages of Totopo, Tolite, and Juria over the last five years. The spatial pattern of flood vulnerability within the watershed is closely linked to morphological features, such as steep slopes, low soil infiltration capacity, and excessive surface flow accumulation—particularly within the Bilato and Boliyohuto sub-districts.